PENGENALAN INSTRUMEN INVESTASI KEPADA WARGA CURUG CUKANG GALIH SEBAGAI UPAYA MENINGKATKAN KESADARAN DALAM BERINVESTASI - Luky Thio (Jurnal Abdi Mandala, 2023)
This service activity aims to gain insight into investment and stock trading, as well as things that investors need to pay attention to before investing. This service is one way to overcome the influence of the low interest of lecturers in investing in the Indonesian Capital Market. This is due to a lack of intrinsic motivation and investment knowledge in lecturers, causing low interest in investing. In addition, this service aims to provide education and outreach about investing in the Indonesian Capital Market to all residents of Cukang Galih, Tangerang. Thisservice also provides a clear picture that with the Investment Education and Training in the Indonesian Capital Market at Cukang Galing Tangerang, it is hoped that this service can become input for participants to gain insight into investing and trading stocks and other things. - Things that investors need to pay attention to before investing.